THE CURRENT ISSUES OF THE US AND CHINA ECONOMIC TRADE RELATIONS: THE CASE OF ZTE CORPORATION (Journal of Economic Research & Business Administration, 2018)
In the article, it is considered the current trade and economic issues between the United States of America and China. In particular, in the given research, it has been studied the urgent problems of trade and economic relations between the United States and China in the field of the international telecommunications industry were studied, in the case of ZTE Corporation. It has been analyzed the current economic, social and political aspects of trade relations between the United States and China in the context of ZTE case. It has been detected advantages and disadvantages for both countries based on economic methodologies and analytical tools. The primary research methodology of this paper is based on conducting the comparative analysis of existing patterns of macroeconomic development, political differences and social issues within China and the US. The given analysis is based on SWOT, PESTEL, Ishikawa cause and effect modeling, risk identification techniques as well as the five forces model by M. Porter detecting competitive advantages for the countries mentioned above. It is also implemented the systematic vision and expert assessment. Moreover, it has been considered the possible solutions and recommendations on how to improve the current economic relations between given countries in the context of the given ZTE corporation.